Analisis Dampak Penggunaan Gadget Terhadap Perilaku Belajar Siswa : Suatu Kajian Literatur - Hanis Ardika Sari; Tini Sondari Royani Putri; Tiyan Ristiyana (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The use of gadgets among students has become a common phenomenon in the digital era. Although gadgets provide easy access to information and support learning, their uncontrolled use can have a negative impact on students' learning behavior. This study aims to analyze the positive impacts, negative impacts, and factors that influence the use of gadgets on students' learning behavior through a literature review method. Data were obtained from nine scientific journals published between 2020 and 2025 and analyzed descriptively-qualitatively. The results of the study show that gadgets can increase students' learning motivation, digital literacy, and access to information if used wisely. However, negative impacts were also found, such as decreased concentration, stress, sleep disturbances, and a tendency towards social isolation. Factors that influence these impacts include duration of use, purpose of use, digital literacy, and parenting patterns and the school environment. This study recommends the importance of the active role of parents and teachers in guiding students so that gadgets are used as a means of supporting learning, not as a distraction from learning focus.